Implementing Learner Autonomy in English as a Foreign Language Classroom Through a Flipped Classroom Pedagogical Approach - Romanyshyn, Ihor; Freiuk, Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
This study is a small-scale action research on the problem of using the Flipped Classroom pedagogical approach to enhance learner autonomy in the target group of high school students in an EFL classroom. The main stages of the research were conducted in the spring semester of the academic year of 2023/24. The participants of the study are seven Ukrainian Grade 9 students and three teachers. The research aims at designing and implementing a method for engaging learners in autonomous practices through the Flipped Classroom model. The methodological basis of this study is the works of (Benson & Voller, 2014), the Flipped Learning Network (2014), (Moore, 2015), (Velegol, Zappe, & Mahoney, 2015), (O’Flaherty & Phillips, 2015), (Hung, 2015), (Huang & Hong, 2016), (Nichols, Burgh, & Kennedy, 2017), (Olakanmi, 2017), (Låg & Sæle, 2019), (Jung, Park, Kim, & Park, 2022), (Little, 2022) and other scientists. In this research, the mixed-method approach is used; the quantitative and qualitative data have been collected through guided observation, surveys (teacher interviews and student questionnaires), and mathematical statistics (descriptive and frequency methods). The essence of the designed method lies in the gradual engagement of students in reviewing short video lectures and reading relevant input before class; then, in class, discussing content and doing quizzes and exercises to reinforce understanding, and, finally, actively participating in creating content-related presentations or projects. The results of this study demonstrate that the Flipped Classroom approach has a considerable impact on learner self-awareness, beliefs, and attitudes implemented in autonomous classroom practices, in particular: effective use of free time for English studying; increased motivation to explore new content and understanding it; perception of a teacher as a facilitator, suggesting a move towards a more student-centered or collaborative learning environment; perception of knowledge as something to be gained rather than “transmitted”, taking on responsibility for evaluating learning outcomes through self-assessment or collaborative evaluation methods. Nevertheless, there are some limitations to using FC in the English language classroom: the willingness of teachers to apply learner-centered methods; the willingness of students to take responsibility for their learning; learners’ cognitive and metacognitive skills; the difficulty of the learning material meant for flipping (self-study), access to resources and technology. The results of this study can be used by researchers and practitioners working in the sectors of secondary and tertiary education.